Development of Microlearning-Oriented Explainer Videos on Robotics Learning in Higher Education - Anak Agung Gde Ekayana (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
The digital era triggers innovation in the learning process where currently, students prefer to find and learn learning resources through the internet/online technology. Microlearning-oriented explainer video media is one solution to accommodate changes in the current way of learning. This research aims to develop and implement microlearning-oriented explainer videos in robotics courses in higher education on a limited scale. The research used the Plomp development model to create explainer videos. The resulting explainer video media is tested for validity, practicality, and effectiveness. The results revealed that the explainer video media that had been developed got excellent results in the aspects of validity and practicality, while the results of testing the effectiveness of the media in the classroom and tested statistically that there were differences in learning achievement between before and after using explainer video media in robotics learning materials. Increased learning achievement of robotics learning materials is evidence of increased student activity and enthusiasm in learning so that learning outcomes can be fulfilled.